2006
DOI: 10.1073/pnas.0600733103
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction of spin-labeled arrestin with inactive and active phosphorhodopsin

Abstract: Arrestins regulate signaling and trafficking of G protein-coupled receptors by virtue of their preferential binding to the phosphorylated active form of the receptor. To identify sites in arrestin involved in receptor interaction, a nitroxide-containing side chain was introduced at each of 28 different positions in visual arrestin, and the dynamics of the side chain was used to monitor arrestin interaction with phosphorylated forms of its cognate receptor, rhodopsin. At physiological concentrations, visual arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
298
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 169 publications
(319 citation statements)
references
References 44 publications
21
298
0
Order By: Relevance
“…2A and Fig. S3), consistent with a more restricted motion for this loop at a direct receptor interaction site (11).…”
supporting
confidence: 55%
See 4 more Smart Citations
“…2A and Fig. S3), consistent with a more restricted motion for this loop at a direct receptor interaction site (11).…”
supporting
confidence: 55%
“…EPR spectra of 139R1 suggested that this loop has high mobility in both the basal and active states (11), consistent with the relatively broad distributions for distances between 139R1 and R1 at reference sites 60, 173, 251, and 267, both in the absence and presence of P-Rh*. All distance changes are consistent with a movement of the 139 loop away from the finger loop, which apparently resides at the receptor-binding surface (11). We propose that the observed large movement of the 139 loop facilitates receptor binding involving the finger loop and adjacent elements.…”
mentioning
confidence: 99%
See 3 more Smart Citations